Optimal Dose of Gell Peptide for Diabetic Wound Healing - Febriani Dina; Mulianto Nurrachmat; Kusumawardani Arie; Julianto Indah; Wardhani Irene Ardiani Pramudya (Syntax Corporation, 2023)
Various studies show that diabetes cases are increasing. Epidemiological data also reported 10.7 million diabetes cases in Indonesia in 2019. Diabetic foot syndrome is a common complication in individuals with DM. Its treatment is costly and prolonged. Thus, we conducted an in vivo study to assess the optimal peptide dose and its effectiveness in accelerating diabetic wound healing. This experimental laboratory study with a randomized pre-post test control group design was conducted in Wistar rats with diabetic wounds receiving different doses of gel peptides. One Way Anova test was applied to compare the effectiveness of the three doses of gell peptide (0.05 gr, 0.1 gr, 0.15 gr). The significance level was determined with P<0.05. Significant improvement in all groups was started on day 7 (p=0.000). The best outcome was obtained in group B, in which the wound had complete closure (p=0.000). The optimal dose of 0.1 gr gell peptide is effective for accelerating diabetic wound healing and closure.